Possibilidades de uso em linguística forense de banco de dados brasileiros de língua e fala - Vieira, Daniel Fonseca (Universidade Federal de São Carlos, 2024)
This project aims to survey language and speech databases in Brazil and assess their potential for use in forensic linguistics tasks. During the survey stage of the research, we identified 45 databases from various regions of Brazil. The survey comprised consultation with experts in sociolinguistics and dialectology and bibliographic research. The assessment of potential usefulness for forensic purposes consisted in the application of a questionnaire addressing general project characteristics, types of materials provided, participant characteristics, geographical coverage, access conditions, and other relevant aspects. As a result, this work systematically presents the survey of language and speech databases in Brazilian Portuguese, enabling the identification of those suitable for generating population distribution statistics of linguistic and phonetic features relevant to the Speaker Comparison task. The generated information will be valuable for experts in forensic linguistics, phonetics, as well as other language-related fields.
Possible use in forensic linguistics of Brazilian language and speech databases
Keywords: Fonética; Linguística forense; Fonética forense; Criminalística; Bancos de dados; Phonetics; Forensic linguistics; Criminalistics; Database; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA